MENINGKATKAN HASIL BELAJAR DENGAN MENGGUNAKAN PENDEKATAN BELAJAR KELOMPOK PADA SISWA KELAS VIII SMP NEGERI 2 BATUSANGKAR - Olce Dwi Putra; Idawati Syarif; Susmiarti Susmiarti (SENDRATASIK UNP, 2013)
Abstract This article was written to describe the used of the group work to improve student’s learning outcomes in the musical art subject at grade VIII7 SMP Negeri 2 Batusangkar. Group work learning approach has a very important role in growing maturity and improve children's ability to master the material whatever they want through learning together to achieve maximum learning. Based on the result of the experiment, it was found that the average score of experimental group was higher than the average score of control group. Based on a t-test, it was obtained that tcounted > tTable, which means that there is a significant difference of learning outcomes between the students who learn by using group work learning approach and conventional  technique in the subjects of Musical Arts at SMP Negeri 2 Batusangkar. This significant difference between the score of learning outcomes of the two classes, the data show that group work learning approach gives positive effect toward learning outcomes at level of confidence 95%. Keywords: Group work learning approach; Musical art; learning outcomes.